Glucose-to-Platelet Ratio as a Biochemical Indicator of Metabolic–Coagulation Imbalance and Mortality Risk in Critically Ill Patients with Ischemic Stroke: A MIMIC-IV Cohort Study: GPR as a Biochemical Marker of Metabolic–Coagulation Imbalance in Ischemic Stroke - Peng, Jie; Zhang, Xingzhan; Wu, Huanhuan; Chen, Hongzhi; Guan, Jianbin; Liu, Zhanguo; Liu, Xingxing (Journal of Medical Biochemistry, 2026)
Background: Early identification of high-risk patients with ischemic stroke in the intensive care unit (ICU) remains challenging. Biochemical markers reflecting the interplay between metabolic stress and coagulation–inflammatory pathways may provide improved prognostic value. The glucose-to-platelet ratio (GPR), a composite index derived from routine laboratory parameters, has emerged as a potential indicator of systemic metabolic–coagulation imbalance; however, its prognostic significance in critically ill ischemic stroke patients has not been fully elucidated.Methods: This retrospective cohort study was conducted using the MIMIC-IV database. Adult patients with ischemic stroke undergoing their first ICU admission and with a length of stay ≥24 hours were included (n = 3686). After excluding patients with missing exposure data, 3536 individuals were analyzed. GPR was calculated as the ratio of the first measured blood glucose (mg/dL) to platelet count (×10⁹/L) within 24 hours of ICU admission. Participants were categorized into quartiles according to GPR levels. Kaplan–Meier survival analysis, multivariable Cox proportional hazards models, and restricted cubic spline analyses were employed to evaluate the association between GPR and 28- and 90-day all-cause mortality.Results: In fully adjusted models, each unit increase in GPR was independently associated with increased risks of 28-day mortality (HR 1.11, 95% CI 1.03–1.21; P=0.009) and 90-day mortality (HR 1.09, 95% CI 1.01–1.17; P=0.002). Compared with the lowest quartile, patients in the highest GPR quartile exhibited significantly elevated risks of 28-day (HR 1.37, 95% CI 1.08–1.75; P=0.010) and 90-day mortality (HR 1.25, 95% CI 1.02–1.54; P=0.034). Kaplan–Meier curves demonstrated significantly reduced survival probabilities with increasing GPR levels (log-rank P